Answer:
![\mathbf{f(22) = (1)/(729)}](https://img.qammunity.org/2021/formulas/mathematics/college/3ubeocpxi46e6jul7lh7l4h4ys1jsww1p7.png)
![\mathbf{f(0) = (1)/((25))}](https://img.qammunity.org/2021/formulas/mathematics/college/xo3w0rhrkuk6pq73ldlegghubko0nv5bts.png)
![\mathbf {f(a) = (1)/((a+5)^2)}}](https://img.qammunity.org/2021/formulas/mathematics/college/iy1ketijmmb919xnw4n4bt9cwgkdrp0p3x.png)
![\mathbf{f(t+22) = (1)/((t+27)^2)}](https://img.qammunity.org/2021/formulas/mathematics/college/ztpuryldvgin9rcks535mv8oc0cisirm6u.png)
![\mathbf{f(x+h) = (1)/((x+h+5)^2)}](https://img.qammunity.org/2021/formulas/mathematics/college/mlv19t24ukdjrkmf6b6nxx3myh79s9gocx.png)
=
![\mathbf{ (-h-2x-10)/((x+h+5)^2(x+5)^2)}](https://img.qammunity.org/2021/formulas/mathematics/college/mj2hbqmbg7ug98kiw9a700etw4xpii1yw1.png)
Explanation:
The mathematical interpretation of the A function f is given by
f(x)equals=StartFraction 1 Over left parenthesis x plus 5 right parenthesis squared End Fraction 1(x+5)2 is :
![f(x) = (1)/((x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hvfnj1vagt0q85ovarrtrvpqquc8sxshoz.png)
So; we are ask to find the following:
a)
f(22) ; i.e what is the function when x = 22
So replacing x = 22 into the above function; we have:
![f(x) = (1)/((x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hvfnj1vagt0q85ovarrtrvpqquc8sxshoz.png)
![f(22) = (1)/((22+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hcuq75yhlk55t6dxo3889vik41vjjfyoip.png)
![f(22) = (1)/((27)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/zw9andb2solw04yj5saa6isr6fdjb08shx.png)
![\mathbf{f(22) = (1)/(729)}](https://img.qammunity.org/2021/formulas/mathematics/college/3ubeocpxi46e6jul7lh7l4h4ys1jsww1p7.png)
f(0) : i.e what is the function when x = 0
So replacing x = 0 into the given function; we have:
![f(x) = (1)/((x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hvfnj1vagt0q85ovarrtrvpqquc8sxshoz.png)
![f(0) = (1)/((0+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/781yz8swib8gral71rqxapzfqjaulevyxy.png)
![\mathbf{f(0) = (1)/((25))}](https://img.qammunity.org/2021/formulas/mathematics/college/xo3w0rhrkuk6pq73ldlegghubko0nv5bts.png)
f(a) : i.e what is the function when x = a
So replacing x = a into the given function; we have:
![f(x) = (1)/((x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hvfnj1vagt0q85ovarrtrvpqquc8sxshoz.png)
![\mathbf {f(a) = (1)/((a+5)^2)}}](https://img.qammunity.org/2021/formulas/mathematics/college/iy1ketijmmb919xnw4n4bt9cwgkdrp0p3x.png)
f(tplus+22), i.e what is the function when x = t+22
So replacing x = t+22 into the given function; we have:
![f(x) = (1)/((x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hvfnj1vagt0q85ovarrtrvpqquc8sxshoz.png)
![f(t+22) = (1)/((t+22+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/jyh38fhoasz3a79uq8knum2emilbw691qp.png)
![\mathbf{f(t+22) = (1)/((t+27)^2)}](https://img.qammunity.org/2021/formulas/mathematics/college/ztpuryldvgin9rcks535mv8oc0cisirm6u.png)
f(xplus+h), i.e what is the function when x =x+h
So replacing x = x+h into the given function; we have:
![f(x) = (1)/((x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hvfnj1vagt0q85ovarrtrvpqquc8sxshoz.png)
![\mathbf{f(x+h) = (1)/((x+h+5)^2)}](https://img.qammunity.org/2021/formulas/mathematics/college/mlv19t24ukdjrkmf6b6nxx3myh79s9gocx.png)
Similarly; another function is given as :
Start Fraction f left parenthesis x plus h right parenthesis minus f left parenthesis x right parenthesis Over h End Fraction f(x+h)-f(x)h.
Mathematically the above function can be expressed as:
![(f(x+h)-f(x))/(h)](https://img.qammunity.org/2021/formulas/mathematics/college/1ax6w1ires59rqu35oz7dq23bzeer4pu8r.png)
where ;
and
![f(x) = (1)/((x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hvfnj1vagt0q85ovarrtrvpqquc8sxshoz.png)
So;
![(f(x+h)-f(x))/(h) = ((1)/((x+h+5)^2) -(1)/((x+5)^2) )/(h)](https://img.qammunity.org/2021/formulas/mathematics/college/y5lj0bu7pvsu9otesw3sr4iz1nqwwy7thu.png)
![=( ((x+5^2)-(x+h+5)^2)/((x+h+5)^2(x+5)^2) )/(h)](https://img.qammunity.org/2021/formulas/mathematics/college/suv0mpa3g1ekx418kxzjg954quo492z5j9.png)
![= (x^2+10x +25-x^2-h^2-25-2xh-10h -10x)/(h(x+h+5)^2-(x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/14niv12nokfppjv0ojy5nf9tqewzg6lacu.png)
![= (h(-h-2x-10))/(h(x+h+5)^2(x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/zno4b4jclzoc3slau3e13bigui36ww0dpb.png)
![=\mathbf{ (-h-2x-10)/((x+h+5)^2(x+5)^2)}](https://img.qammunity.org/2021/formulas/mathematics/college/m8ojvw1ex4dviqqkurkrw3647bff88jubq.png)
b) Note that f could also be given by
f(x)equals=StartFraction 1 Over x squared plus 10 x plus 25 EndFraction
1×2+10x+25
Explain what this does to an input number x.
The mathematical expression of the function is:
![f(x) = (1)/((x^2+10x + 25))](https://img.qammunity.org/2021/formulas/mathematics/college/144eozo0301l2a94sf0c5wdw0ilq4q2nwq.png)
the input = x ; so 5 is added to the i.e x+ 5;
After that the square of the entity (x+5) is taken giving rise to (x+5)²
then the reciprocal of the function is taken ; which now becomes:
![f(x) = (1)/((x+5)^2)](https://img.qammunity.org/2021/formulas/mathematics/college/hvfnj1vagt0q85ovarrtrvpqquc8sxshoz.png)
If we expand the quadratic expression in the bracket; we have:
x being multiplied by the square ² which = x²
then x is multiplied by the addition of (5+5 )x to give 10x
Finally 5 is multiplied by the square ² which = 5² = 25
After the addition of all this three together ; the reciprocal was taken to get:
![f(x) = (1)/((x^2+10x + 25))](https://img.qammunity.org/2021/formulas/mathematics/college/144eozo0301l2a94sf0c5wdw0ilq4q2nwq.png)